Referent Cueing, Position, and Animacy as Accessibility Factors in Visually Situated Sentence Production - Esaulova, Yulia; Penke, Martina; Dolscheid, Sarah (Frontiers in Psychology, 2020)
Speakers’ readiness to describe event scenes using active or passive constructions has previously been attributed – among other factors – to the accessibility of referents. While most research has highlighted the accessibility of agents, the present study examines whether patients’ accessibility can be modulated by means of visual preview of the patient character (derived accessibility) as well as by manipulating the animacy status of patients (inherent accessibility). Crucially, we also examined whether effects of accessibility were amenable to the visuo-spatial position of the patient by presenting the patient character either to the left or to the right of the agent. German native speakers were asked to describe drawings depicting event scenes while their gaze and speech were recorded. Our results show that making patients more accessible using derived and inherent accessibility factors led to more produced passives, shorter speech onsets, and a reduction of fixations on patients. Complementing previous research on agent accessibility, our findings demonstrate that the accessibility of patients affected both sentence production and looking behavior. While effects were observed for both inherent and derived accessibility, they appeared to be more pronounced for the latter. Regarding character position, we observed a significant effect of position on participants’ gaze patterns and structural choices, suggesting that position itself can be considered an accessibility-related factor. Importantly, the position of a patient also interacted with our manipulation of its accessibility via visual preview. Participants produced more passives after preview than no-preview for left-positioned but not for right-positioned patients, demonstrating that effects of patient accessibility (i.e. visual preview) were susceptible to character position. A similar interaction was observed for participants’ viewing patterns. These findings provide the first evidence that the position of a referent is a factor that interacts with other accessibility-related factors (i.e. cueing), emphasizing the need of controlling for position effects when testing referent accessibility.